2022
DOI: 10.1111/eufm.12359
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility in share repurchases: Evidence from UK

Abstract: Although firms cite flexibility as important when repurchasing shares, we know little about how or why firms vary repurchases. We use an extensive sample of daily repurchase transactions from the United Kingdom to investigate how the number of repurchase days and volumes of shares repurchased change based on several known motivations. We find that stock price changes, liquidity, leverage, takeover activity and earnings per share targets impact share repurchasing patterns. Further, we compare actual repurchases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
(135 reference statements)
0
2
0
Order By: Relevance
“…However, there is also evidence that the value creation executives seek via repurchases is not significant (Oded and Michel 2018). Nonetheless, there are other ethical reasons for undertaking repurchases (Hamouda and McMillan 2021), such as dividend substitution and increasing market liquidity (Kulchania and Sonika 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there is also evidence that the value creation executives seek via repurchases is not significant (Oded and Michel 2018). Nonetheless, there are other ethical reasons for undertaking repurchases (Hamouda and McMillan 2021), such as dividend substitution and increasing market liquidity (Kulchania and Sonika 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most recent studies find that the implementation is more likely due to factors such as a firm's positive earnings and larger asset base (Sonika et al 2014), while the completion of repurchases is more likely due to factors such as market capitalisation and increased leverage (Andriosopoulos et al 2013). There was a recent study that focused on the completion period only (Kulchania and Sonika 2023), and that found that adjusting the earnings ratio and debt exposure is influential.…”
Section: Literature Reviewmentioning
confidence: 99%